Mean-variance & mean-VaR portfolio selection: A simulation based comparison in the Czech crisis environment - Radovan Parrák; Jakub Seidler (Charles University in Prague, Institute of Economic Studies (IES), 2010)
This paper focuses on two methods for optimum portfolio selection. We compare Mean-Variance method with Mean-VaR method by the means of investment simulation, based on Czech financial market data from turbulent market periods of the year 2007 and the year 2008. We compare both strategies, basing on measurements of relative and absolute profitability of both strategies in crisis periods. The results indicate that both strategies were relatively profitable in both simulation periods. As a consequence of our results, it seems that it is worth to adhering investment decisions to outputs of optimisation algorithms of both methods. Moreover, we consider Mean-VaR strategy to be safer in turbulent times.
Keywords: C52; G01; G11; 330; portfolio optimization; investment strategy; Mean-Variance; Mean-Var; Portfolio-Management; Theorie; Risikomaß; Tschechische Republik